Spatial profiling of chromatin accessibility in formalin-fixed paraffin-embedded tissues - Pengfei Guo; Yufan Chen; Liran Mao; Angelysia Cardilla; Chin Nien Lee; Yan Cui; Dengge Jin; Yucong Hua; Xiaowei Xu; Yanxiang Deng (Nature Communications)
Abstract Formalin-fixed paraffin-embedded (FFPE) samples represent a vast, untapped resource for epigenomic research, yet molecular tools for deep analysis of these specimens remain limited. We introduce spatial FFPE-ATAC-seq, an approach for in situ profiling chromatin accessibility within archived tissues. This approach overcomes formalin-induced crosslinking challenges, allowing high-resolution mapping of chromatin landscapes while preserving tissue architecture. Applying spatial FFPE-ATAC-seq to mouse and human tissues, including brain and thymus, reveals intricate spatial organization and distinct cell types in alignment with tissue morphology. Integration with single-cell RNA sequencing validates the precision of our chromatin profiles in identifying key cell types and regulatory elements. We further apply this method to human melanoma, comprehensively characterizing chromatin accessibility across both tumor and non-tumor regions. This method significantly expands the toolkit for epigenomic research, unlocking the potential of an extensive collection of archived FFPE samples for studying gene regulation and disease mechanisms with spatial context.